Pengaruh Model Pembelajaran Kooperatif Tipe TGT (Team Games Tournament) Berbantuan Media Questions Box Terhadap Hasil Belajar Siswa Pada Pembelajaran IPA di Kelas III SD - Luthfi Khoirunnisa; Nurrohmatul Amaliyah (Postgraduate, University of Mataram, 2023)
This research aims to determine the effect of the TGT (Time Games Tournament) type cooperative learning model assisted by Questions Box media on the science learning outcomes of Class 3 students at SD Negeri 03 Pagi, even during the semester of the 2022/2023 academic year. The sample for this research was Class III-A at SD Negeri 03 Pagi with a total of 30 students and Class III-B with a total of 30 students. The prerequisite is the normality test which obtains a normal distribution of experimental and control class data. Testing the hypothesis using the t-test obtained a value of t = 9.49, resulting in Ho being rejected at a significance level of 5% with an effect size of 1.54, including the high group. The average score for the control class was 60.50, and the experimental class average was 86.50. These findings indicate that the use of the TGT (Time Games Tournament) type cooperative learning model assisted by Questions Box media has an impact on science learning outcomes in class III of SD Negeri 03 Pagi